2018
DOI: 10.48048/wjst.2019.4436
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermal and Fire Retardant Characteristics of NR/PP/ATH Thermoplastic Vulcanizates

Abstract: Blends of natural rubber (NR) and polypropylene (PP) were melt-mixed with phenolic resin crosslinking agent to obtain thermoplastic vulcanizates (TPVs). The blend composition of NR and PP was at 60/40 %wt. Alumina trihydrate (ATH) was incorporated into the blends to improve the flame retardancy, and the effect of ATH incorporation at different levels (20 - 120 PHP, part per hundred polymers) on blend morphology, ATH dispersion, mechanical properties, thermal resistance and flame retardancy was investigated. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The decrease in elongation at break might be due to a decrease in ductility associated with the incorporation of an excess of metal oxide fillers into the polymer matrix. Such decreasing tensile strength and elongation at break with high load filler was also reported by Datta et al (2016), Yuhaida et al (2016), Onuoha et al (2017), Poltabtim et al (2018), andLopattananon et al (2019).…”
Section: Tensile Properties Before and After Agingsupporting
confidence: 72%
“…The decrease in elongation at break might be due to a decrease in ductility associated with the incorporation of an excess of metal oxide fillers into the polymer matrix. Such decreasing tensile strength and elongation at break with high load filler was also reported by Datta et al (2016), Yuhaida et al (2016), Onuoha et al (2017), Poltabtim et al (2018), andLopattananon et al (2019).…”
Section: Tensile Properties Before and After Agingsupporting
confidence: 72%
“…The first step registered at about 186–305°C was related to simultaneous decomposition of paraffinic oil and deacetylation of EVA. 7,32,33 The second step was in a range of 302–433°C, corresponding to NR degradation upon heating. 7,33 The third step was at 425–520°C due to thermal decomposition of polyethylene (PE) chain after elimination of acetic acid from EVA.…”
Section: Resultsmentioning
confidence: 99%
“…7,32,33 The second step was in a range of 302–433°C, corresponding to NR degradation upon heating. 7,33 The third step was at 425–520°C due to thermal decomposition of polyethylene (PE) chain after elimination of acetic acid from EVA. 7,32,34 The data in Table 3 showed that the onset decomposition temperature (T d5 ) , maximum decomposition temperature of paraffinic oil/deacetylation of EVA (T dmax1 ), NR (T dmax2 ), EVA (T dmax3 ) and residual weight of prepared EVA/NR blend nanocomposite foams without SiO 2 through DM approach were closed to those of PSM method.…”
Section: Resultsmentioning
confidence: 99%